Countering the threat of Daesh in Malaysia - El-Muhammady, Ahmad (Konrad Adenauer Stiftung; S. Rajaratnam School of International Studies (RSIS), 2016)
It is reported that between February 2013 to 2015, Malaysian police have arrested 107 individuals for allegedly attempting to join Daesh or Daesh-affiliated groups in Syria and Iraq. In May 2016, four Malaysians appeared in Daesh media al-Barakah, burning their passports and declaring war against the Malaysian government. Malaysian authorities believe that they are members of Katibah Nusantara which were responsible for the Jakarta attack on 14 January 2016. In June 2016, one Malaysian appeared again in a Daesh-produced video. This time he openly declared war against the Malaysian police and the taghut regime, before proceeding to slaughter three individuals suspected of being spies. The police later identified the person as Mohd Rafi Udin, a former member of Kumpulan Mujahidin Malaysia (KMM) and a former Internal Security Act (ISA)1 detainee. This alarming trend indicates that the Daesh threat is not diminishing despite the fact that they are losing ground in Syria and Iraq. Given the gravity of the issue, this article essentially attempts to discuss four interrelated issues: (1) threats to Malaysia’s national security, 1967-2015; (2) the emergence of Daesh-affiliated groups in Malaysia; (3) motivations for Malaysians to join Daesh; and (4) approaches taken by the Malaysian government and civil society in tackling the Daesh threat in Malaysia.